60 years of dislocations in ceramics: A conceptual framework for dislocation mechanics in ceramics. Issue 4 (20th June 2022) - Porz, Lukas
Abstract: High‐tech ceramics are typically engineered by controlling point defects and interfaces while one‐dimensional dislocations have found much less attention so far. Nevertheless, their impact on almost any functional property and the sudden ease to fabricate them with novel synthesis methods, such as rapid densification, brings spotlight attention to dislocations as design dimension. Although the typical brittleness of ceramics insinuates the irrelevance of dislocations for mechanical behavior, abundant literature is spread over materials, decades, and disciplines, however, often unconnected. Here, a conceptual framework for dislocation mechanics in ceramics separated into five logical aspects, (1) fundamental mobility, (2) obstacles to motion, (3) limitation by necessity of nucleation, (4) motion complexity, and (5) avoidance of competing mechanisms, brings oversight into the complex behavior. In consequence, quicker identification of the limiting step allows to estimate the potential involved more precisely and to identify open research questions with greater ease. An introduction to dislocations and the functionality involved, a look back over the last six decades, and highlights of open question are dedicated to provide a framework and bridge the gap between the attached research fields.